Society 5.0 , datafication and the illusion of lawlessness - Zulhuda, Sonny (2021)
The obsession of Society 5.0 as launched by the Government of Japan in 2016 is to incorporate modern technologies such as Big Data, the Internet of Things (IoT), robotic technology and Artificial Intelligence in all industries and social activities to achieve both economic development and solutions to social problems in parallel. The ongoing transformation of the information society has indeed guaranteed the dynamic in the society. Businesses, governance, works, education, social bonding and family values are being redefined in the wake of the massive adoption of digital technologies. This transformation, which had begun long before the launching of Society 5.0 itself, often leaves us with many legal questions that remain unanswered. Despite efforts by parliaments and judiciary worldwide in regulating the digital transformation and its legal consequences, we still see the dynamic that keeps our society preoccupied. Looking at these legal concerns will get us more prepared when shifting to this Society 5.0. Legal anomalies such as the spread of hoaxes and online scams, breach of digital privacy, abuse of personal data for pecuniary gains, and online predatory behaviour are haunting our shared space and may eventually hinder the full benefit of the datafication. Behind these anomalies is the false sense of unassailability of the Internet, i.e. the belief that cyberspace is a lawless space. The absence of physical presence of authority, among others, leads to this myth of anonymity, hence the wrongdoing and crimes are committed. This false sense of unassailability of the Internet, if ignored, will only become the continuing source of more anomalies in future. In this keynote, and drawing from some high-profile cases, the author discusses this false sense of unassailability that led to the illusion of lawlessness, absolute freedom of expression, and data abuses in the context of the information society. It also incites some preliminary thoughts on what can be done to address the concern. The author hopes this will further raise the interest of fellow researchers to work on this area in future.